Prune-belly syndrome: an autopsy case report - Marcela Arruda Pereira Silva Vasconcelos; Patrícia Picciarelli de Lima (University of São Paulo, 2014)
Prune-belly syndrome (PBS) is a rare congenital anomaly characterized by a spectrum of mild-to-severe presentations of urinary tract malformations, deficient abdominal wall musculature, and cryptorchidism in male newborns or genital abnormalities in the female newborns. Currently, antenatal diagnosis is feasible with ultrasound examination, and treatment is based on case report experience. More recently, intrauterine management has been undertaken with encouraging results. The authors report a case of PBS diagnosed at the seventeenth gestation week, when ultrasonographic examination revealed the presence of ascites, distended bladder, thickened bladder wall and posterior urethral valve. The fetus was submitted to an intrauterine intervention at the nineteenth gestational week. Delivery occurred at 34 weeks of gestation and the newborn examination was consistent with PBS. On the second day of life, the newborn was submitted to abdominoplasty, colostomy, and orchiopexy. However, the outcome was unfavorable with respiratory failure and death on the fifteenth day of life. The autopsy confirmed the diagnosis of PBS, but the immediate cause of death was attributed to aspiration pneumonia.